A qualitative study on the evolving drivers for employee engagement in the Malaysian service sectors post-Covid - Nadarajan, Nishalina (2024)
The unprecedented global crisis, COVID-19 impacted us in many ways, our health was at stake, suddenly the economic situation became very volatile and businesses suffered to survive. Throughout these tough times, we were forced to function within the ‘new normal’ of both life and ways of working. The entire work landscape experienced a swift change with new possibilities of working. Technology took the forefront of everyday connect with a sharp rise in usage and adaptability. Organizations were taught to rethink new, innovative ways of doing business to stay relevant. New terms like Work from Home (WFH), platforms such as Teams or Zoom quickly became a familiar mode of connect, and health and well-being became a priority for many. The pre-Covid days saw employee engagement led by employers being instrumental in contributing towards employee happiness, increased productivity, and job satisfaction. However, after the pandemic, the situation has changed extensively and employees are now more demanding of what they feel is important to stay engaged. With the different ways of working and shift in prioritisation, literature has suggested possible evolvement in employee engagement drivers in a post-Covid work environment. Existing literatures on engagement mostly cover the time frame of pre-Covid and during the pandemic, while post-Covid studies on the subject is limited. Given the above gap, the intend of this study is to identify the impact of Covid-19 on employee engagement, explore the key drivers for employee engagement in a post-Covid situation and identify the effect of well-being, job satisfaction, flexibility, and reward on employee engagement. As the drivers of employee engagement may have evolved, the findings of the study will reveal the current drivers for a high employee engagement level amongst the employees in the Malaysian service sector. This study adopts the qualitative research approach using the convenience sampling technique. The non-probability and non-random sampling method is used as it involves participants from a targeted population that fulfils the criteria of the study with easy accessibility, geographical nearness, accessibility at a definite time, and readiness to partake in the interview. The data is obtained through the technique of interview via Microsoft Teams to identify their current engagement drivers today. In summary, the findings indicate that the engagement drivers have significantly evolved, which if not provided by employers today, may be even impact employee retention level or be a reason of one rejecting a potential job offer. The impact of Covid-19 on employee engagement has certainly provided new experiences and opportunities in performing work in a different way. Further recommendations have been provided, grounded by extensive literature review and findings garnered. This study also contributes to the existing research and literature limitations as the evolvement of engagement drivers in a post-COVID work environment in a Malaysian context is still inadequate.